A Systematic Approach to Teaching Case Studies and Solving Novel Problems - Carolyn A. Meyer (American Society for Microbiology, 2018)
Both research and practical experience in education support the use of case studies in the classroom to engage students and develop critical thinking skills. In particular, working through case studies in scientific disciplines encourages students to incorporate knowledge from a variety of backgrounds and apply a breadth of information. While it is recognized that critical thinking is important for student success in professional school and future careers, a specific strategy to tackle a novel problem is lacking in student training. We have developed a four-step systematic approach to solving case studies that improves student confidence and provides them with a definitive road map that is useful when solving any novel problem, both in and out of the classroom. This approach encourages students to define unfamiliar terms, create a timeline, describe the systems involved, and identify any unique features. This method allows students to solve complex problems by organizing and applying information in a logical progression. We have incorporated case studies in anatomy and neuroanatomy courses and are confident that this systematic approach will translate well to courses in various scientific disciplines.